Application of a unified probabilistic framework to the dose-response assessment of acrolein. (October 2020) - Blessinger, Todd; Davis, Allen; Chiu, Weihsueh A.; Stanek, John; Woodall, George M.; Gift, Jeff; Thayer, Kristina A.; Bussard, David
Highlights: Example application of unified probabilistic framework. Computation of probabilistic reference value for nasal lesions for acrolein. Probabilistic reference value slightly lower than traditional reference value. Adjustments to distributions of variable components yields varying reference values. Abstract: Background: In quantitative chemical risk assessment, a reference value is an estimate of an exposure to a chemical that is "likely to be without appreciable risk." Because current "deterministic" approaches do not quantitatively characterize the likelihood or severity of harm, the National Academies has recommended using reference values derived from a risk-specific dose that are treated as random variables, with probability distributions characterizing uncertainty and variability. Objectives: In order to build familiarity and address issues needed for routine and standardized derivation of probabilistic risk-specific dose distributions, a case example applying the unified probabilistic framework presented in Chiu and Slob (2015) is developed for acrolein. This case study is based on an updated systematic evidence map of literature (Keshava et al., 2020) identifying nasal lesions reported in Dorman et al. (2008) as the most appropriate endpoint and study for reference value derivation. Methods: The probability distribution was calculated for the risk-specific dose, which in this implementation of the approach was calculated for the dose at which 1% of the human population is estimated to experience minimal lesions, and a probabilistic reference value was computed as the 5th percentile of this distribution. A deterministic reference value was also derived for comparison, and a sensitivity analysis of the probabilistic reference value was conducted investigating alternative assumptions for the point of departure type and exposure duration. Results: The probabilistic reference value of 6 × 10 −4 mg/m 3 was slightly lower than the deterministic reference value of 8 × 10 −4 mg/m 3, and the risk-specific dose distribution had an uncertainty spanning a factor of 137 (95th-5th percentile ratio). Sensitivity analysis yielded slightly higher probabilistic reference values ranging between 9 × 10 −4 mg/m 3 and 2 × 10 −3 mg/m 3 . Conclusions: Using a probabilistic approach for deriving a reference value allows quantitative characterization of the severity, incidence, and uncertainty of effects at a given dose. The results can be used to inform risk management decisions and improve risk communication.